The relationship between work and mental health outcomes in Black men after serious injury. Issue 4 (April 2021) - Palumbo, Aimee J.; Richmond, Therese S.; Webster, Jessica; Koilor, Christopher; Jacoby, Sara F.
Highlights: For black men who survive serious injuries, work-related factors are associated with mental health recovery. Men who had not returned to work had twice the odds of poor mental health than men who had returned to work. Experiences of racism and health insurance status were also associated with mental health outcomes after injury. Abstract: Objectives: To explore the association between return to work (RTW) and mental health outcomes in Black men in Philadelphia recovering from serious traumatic injuries. Methods: We analyzed data from 498 Black men aged ≥ 18 years living in Philadelphia who were admitted to a Level I trauma center for injury between January 2013 and June 2017. We used multivariable logistic regression to estimate the association between pre-injury occupation, RTW and depression or PTSD 3 months after hospitalization. Results: In adjusted analyses, men who had not RTW at follow-up had higher odds of poor mental health outcomes than men who had RTW (OR: 2.7, 95% CI: 1.8, 4.2). Additional significant factors included: younger age, lack of or public health insurance and higher lifetime experiences of racism. Conclusions: The mental health recovery trajectory of injured Black men living in Philadelphia is associated with RTW and other factors that can influence financial stability and economic resources. Policy implications: Programmatic strategies that seek to optimize recovery after injury in Black men should include consideration of key structural factors such as employment, financial stability, and the impact of racism-related exposures.